The Impact of The Marketing Mix on The Development of Banking Services in the Financial Investment Bank - Ibrahim, Ashwag Sied Ali (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to highlight the role that the marketing mix plays in the quality of banking services. The study discussed the use of auxiliary tools of the marketing mix and their impact on the quality of banking services. The study followed the descriptive and analytical approach. The study reached a number of results, the most important of which is the existence of a statistically significant relationship between the elements of the marketing mix and the development of banking services. At the Financial Investment Bank, there is a statistically significant relationship between the comprehensive quality plans for the marketing mix and banking services at the Financial Investment Bank. The study proved the presence of a human cadre gifted with experience and understanding of comprehensive quality functions, which is reflected in the development of banking services. The senior management at the Financial Investment Bank provides all quality needs, which is reflected On the quality of the marketing mix, and conducting training courses helps develop banking services.
Keywords: Marketing mix; banking services quality; marketing environment; financial investment bank